Feasibility Study & Investment Analysis – Textile Machineries at PT Heksatex - Adriano, William; Anggono, Achmad Herlanto (The Indonesian Journal of Business Administration, 2013)
The Spacer fabric production from PT Hexsatex number is very increasing by the year ,it can be seen from the history of the production increase due to increase in demand from 2006 to 2011. The need of spacer fabric varies from the base material product shoe products, furniture, mattresses, bags, garmentand accesories, and various other needs . Based on the customer needs, the company strives to provide availability of productson the market. In fact, the production capacity of PT Hexsatex machine is still limited and not comparable with increasing demand from the market. However, this research through the end of the project to carry out an analysis of the new machine investment Spacer fabric to enhance the production capacity of PT Hexsatex. In conducting investment analysis of new engines for PT Heksatex, researchers conducted a financial analysis to drive the machine, through the analysis of financial lease or operating lease, which is more profitable for the company. Once these aspects are fulfilled researchers to analyze cash flow predictions, Payback Period, Net Present Value, Interest Rate Return, and Profitability Index. Based on this analysis can be said to be feasible if the value of the project NPV is greater than zero and IRR greater than theWACC. As foraspects of production estimates PT Heksatex will choose the estimated sales optimist. Based on the financialanalysis of the PT Heksatex choose leasing options with optimistic estimates. The option shave a NPV>0,IRR>WACC, and a payback period of 5 years. From the analysis of the analysis showed that the advantage of this option, especially because the cost is lower.Â Key Words: Spacer fabric machine, New investment, Financial Aspect, NPV, IRR, and Optimistic estimate.